Kemampuan Literasi Matematika Siswa dalam Menyelesaikan Soal Matematika Tipe HOTS Berdasarkan Gender - Sri Rahayu; Aprisal Aprisal; Fauziah Hakim; Yusfa Lestari (FKIP Universitas Mataram, 2025)
Mathematical literacy is a fundamental cognitive competency that enables students to analyze mathematical situations and communicate their reasoning effectively. Although numerous studies have investigated mathematical literacy, research that specifically examines students’ performance on HOTS-type mathematical tasks from a gender perspective remains scarce. This study aims to describe students’ mathematical literacy skills in solving HOTS problems based on gender differences. Employing a descriptive qualitative design, the study involved 35 students from class XII IPA 1, consisting of 7 males and 28 females. Data were collected through tests and semi-structured interviews, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that in analyzing-type HOTS items (C4), male students generally met only the communication indicator, with one male student demonstrating mastery of all indicators. Conversely, female students consistently fulfilled all mathematical literacy indicators. A similar pattern emerged in evaluating-type HOTS items (C5), where most male students achieved only the communication indicator, while female students met all indicators. In creating-type HOTS items (C6), both male and female students demonstrated achievement solely on the communication indicator.